Synergistic Integration of Human Capital, Transportation Optimization, and Digitalization in Logistics Efficiency: Integrasi Sinergis Modal Manusia, Optimasi Transportasi, dan Digitalisasi dalam Efisiensi Operasional Logistik - Muhammad Sodik (Journal of State Economic Research, 2025)
This study examines the synergistic integration of human capital, transportation optimization, and digitalization in enhancing logistics efficiency. Employing a mixed-methods approach, quantitative data were collected from 150 logistics firms across Indonesia through structured questionnaires and analyzed using structural equation modeling. Qualitative interviews with industry experts complemented the findings, offering contextual insights into operational challenges. The results indicate that human capital competencies significantly influence transportation optimization strategies, while digitalization acts as a critical mediator that amplifies the impact of both factors on logistics performance. Specifically, investment in employee training and skill development improves route planning and resource allocation, whereas advanced digital platforms facilitate real-time tracking, data analytics, and process automation. The integrated model explains 68% of the variance in logistics efficiency, highlighting the importance of coordinated investment across human, physical, and technological resources. Implications for policymakers and practitioners include prioritizing workforce development and digital infrastructure to achieve sustainable competitive advantage in the logistics sector.